2014
DOI: 10.4269/ajtmh.13-0728
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Targeted Typhoid Vaccination Campaign Following Cyclone Tomas, Republic of Fiji, 2010

Abstract: Abstract. After a category 4 cyclone that caused extensive population displacement and damage to water and sanitation infrastructure in Fiji in March 2010, a typhoid vaccination campaign was conducted as part of the post-disaster response. During June-December 2010, 64,015 doses of typhoid Vi polysaccharide vaccine were administered to persons 2 years of age, primarily in cyclone-affected areas that were typhoid endemic. Annual typhoid fever incidence decreased during the post-campaign year (2011) relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 10 publications
(11 reference statements)
0
53
0
Order By: Relevance
“…Typhoid Vi polysaccharide vaccines have been used in mass vaccination campaigns in several Asian countries where typhoid fever is endemic and its epidemiology is well understood. 12,16,18,19 The success of vaccination campaigns has influenced WHO to recommend consideration of the use of these vaccines to target high-risk groups in countries where typhoid is endemic and to control epidemics. 12 Social scientists have investigated behavioral, sociocultural, political, and economic factors that may influence vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Typhoid Vi polysaccharide vaccines have been used in mass vaccination campaigns in several Asian countries where typhoid fever is endemic and its epidemiology is well understood. 12,16,18,19 The success of vaccination campaigns has influenced WHO to recommend consideration of the use of these vaccines to target high-risk groups in countries where typhoid is endemic and to control epidemics. 12 Social scientists have investigated behavioral, sociocultural, political, and economic factors that may influence vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Value a and 90% confidence interval estimated for highly endemic Asian settings [13]. In Uganda the Gross Domestic Product per capita is US$ 598 and so, based on WHO standard measures for cost-effectiveness, this intervention would be classified as highly cost-effective [28].…”
Section: Itemmentioning
confidence: 99%
“…One ViCPS vaccine manufactured by Sanofi Pasteur is licensed in many countries for persons 2 years of age and older and is WHO pre-qualified. The ViCPS vaccine has been widely adopted for programmatic use, to control outbreaks in a school in China, and in a preemptive mass vaccination campaign in Fiji following a tropical cyclone [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are few instances of use of typhoid vaccine in post-disaster situation e.g. following a cyclone in Fiji [9] and following complex disasters in Tajikistan and Iran [5]. The study in Fiji demonstrated that the introduction of typhoid vaccine in the post-disaster stage could reduce the incidence of typhoid cases in an endemic region.…”
Section: Introductionmentioning
confidence: 96%